"Latinitas" in the Polish Crown and the Grand Duchy of Lithuania - Siedina, Giovanna (2014)
The volume contains articles concerning the influence of Latinitas in the territory now occupied by Poland, Lithuania, Ukraine and Belarus'. The articles, all published in English, range from history to literature and to cultural history and the history of ideas. They analyze the issue of building an identity, either real or imagined, from different points of view. Among the most interesting topics are the classical origins of myths and ideas that have helped build the national identities of those that constituted the ethnic mosaic of the Grand Duchy of Lithuania and the role of Neo-Latin poetry, as a conveyor of Latinitas, in the development of national identities. Because of the significance of Latinitas for both common European cultural traditions and the national cultures, literatures and languages of Belarus, Poland, Lithuania, Estonia, Latvia and Ukraine, it is to be hoped that the subject will continue to attract a good level of attention in the future